The Effect of Motivation, Compensation, and Training on Employee Productivity (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study wants to explain in detail the influence of motivation, compensation and service on employee productivity. Collecting data in this study using quantitative methods. Processing data using a purposive sampling technique. As for the research sample, namely employees who work at PT Inalum. The results of the study show that by providing great motivation to employees, employee performance is considered to be more productive. Compensation is also essential in increasing employees' morale at PT Inalum. By providing payment to employees, employees will be more diligent in carrying out their respective duties, likewise with training which has a vital role in honing every employee's abilities at PT Inalum. It can be concluded that motivation, compensation and training greatly influence employee work productivity.